2020
DOI: 10.1136/bmjopen-2019-035988
|View full text |Cite
|
Sign up to set email alerts
|

Improving regional care in the last year of life by setting up a pragmatic evidence-based Plan–Do–Study–Act cycle: results from a cross-sectional survey

Abstract: ObjectivesTo set up a pragmatic Plan–Do–Study–Act cycle by analysing patient experiences and determinants of satisfaction with care in the last year of life.DesignCross-sectional postbereavement survey.SettingRegional health services research and development structure representing all health and social care providers involved in the last year of life in Cologne, a city with 1 million inhabitants in Germany.Participants351 bereaved relatives of adult decedents, representative for age and gender, accidental and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 50 publications
0
23
0
1
Order By: Relevance
“…The situation is similar in a longer period of the last 12 months of life [ 5 , 6 , 8 , 11 , 12 ]. The proportion of people who had been admitted at least once to hospital, nursing home or hospice in the LYOL ranged from 54% (France) to 76% (Austria, Israel, Slovenia) [ 11 ] while in Cologne (Germany) the value reached 91% [ 9 ]. In an Australian study nearly all of the decedents spent time in hospital with a marked increase in hospitalizations in the last 108 days of life for people who died of cancer [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The situation is similar in a longer period of the last 12 months of life [ 5 , 6 , 8 , 11 , 12 ]. The proportion of people who had been admitted at least once to hospital, nursing home or hospice in the LYOL ranged from 54% (France) to 76% (Austria, Israel, Slovenia) [ 11 ] while in Cologne (Germany) the value reached 91% [ 9 ]. In an Australian study nearly all of the decedents spent time in hospital with a marked increase in hospitalizations in the last 108 days of life for people who died of cancer [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found transitions increase in the last months of life [1][2][3][4][5], with most of them concerning hospitalization [1,3,4,[6][7][8]. The frequent hospital attendance at this stage of life contradicts most patients' preference for home-based care [7,9,10]. The situation is similar in a longer period of the last 12 months of life [5,6,8,11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 As shown in the Last Year of Life Study Cologne (LYOL-C) Part I Status Quo Report, 42.2% of the Cologne population died in hospitals. 5 Almost 30% of hospital patients are in their last year of life, 6 and 75% of deaths are from conditions other than cancer. 7 Other literature shows that 40%-50% of patients who died in hospitals could have died in the community with better support and training.…”
Section: Introductionmentioning
confidence: 99%
“…As reported by a representative sample of relatives, general hospital units are the most important checkpoints for transitions in the last year of life (eg, diagnosis of 'entering' the last year of life, hospitals as one of the five most frequent care transitions in the last year of life and place of death). 5 Yet, satisfaction in general hospital units is lowest among all health services, especially in comparison to care at home and in nursing homes. Therefore, LYOL-C II aims to test an intervention for general acute hospital units by using a two-sided (healthcare professionals (HCPs) and patients) trigger question-based intervention to 'shake' the system in a minimally invasive manner.…”
Section: Introductionmentioning
confidence: 99%